2014
DOI: 10.4172/1948-5948.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Content, Salinity and pH on Spirulina platensis for Phycocyanin, Allophycocyanin and Phycoerythrin Accumulation

Abstract: The cyanobacterium Spirulina platensis is an attractive source of the biopigment, which is used as a natural colour in food, cosmetic, pharmaceutical products and have tremendous applications in nutraceuticals, therapeutics and biotechnological research. The present study examines the possibility of increasing the content of Phycocyanin, Allophycocyanin, Phycoerythrin and Carotenoids under stress conditions including different pH, salinity and carbon content in S. platensis isolated from Jalmahal, Jaipur (Raja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…La salinidad es un parámetro de cultivo que afecta la fisiología de Spirulina (Sreevani, Bhanumathi, Mohammad, & Murthy, 2011;Sharma, Kumar, Irfan, & Dut, 2014), ejerciendo su efecto en el crecimiento, la síntesis de clorofila a, la ficocianina y los carotenoides (Lamela & Márquez, 2000;Murugan & Rajesh, 2014;Sharma et al, 2014); sin embargo, muchos aspectos fisiológicos, relacionados con la aclimatación, la tolerancia al estrés, la producción de macromoléculas y el crecimiento en medios salinos permanecen sin esclarecer.…”
Section: Discussionunclassified
“…La salinidad es un parámetro de cultivo que afecta la fisiología de Spirulina (Sreevani, Bhanumathi, Mohammad, & Murthy, 2011;Sharma, Kumar, Irfan, & Dut, 2014), ejerciendo su efecto en el crecimiento, la síntesis de clorofila a, la ficocianina y los carotenoides (Lamela & Márquez, 2000;Murugan & Rajesh, 2014;Sharma et al, 2014); sin embargo, muchos aspectos fisiológicos, relacionados con la aclimatación, la tolerancia al estrés, la producción de macromoléculas y el crecimiento en medios salinos permanecen sin esclarecer.…”
Section: Discussionunclassified
“…The average size of synthesized silver nanoparticles synthesized by Abelia grandiflora was 100nm and the shape of the silver nanoparticles proved to be spherical in nature [21]. The SEM image showed that the synthesized silver nanoparticles from (Jasminum sambac L.) were cluster and their size ranged from 14-17nm.…”
Section: Scanning Electron Microscopy(sem)mentioning
confidence: 94%
“…The experimental organism S. platensis was isolated from Kodai road, Dindugal, Tamilnadu (India) and cultivated in Zarrouk's medium under 30±2°C temperature and illuminated with white fluorescent lamps at a light intensity of 2,000 lux (Sharma et al 2014) [5].…”
Section: Methodsmentioning
confidence: 99%
“…In an Erlenmeyer flask, 5 g (dry weight) S. platensis biomass was suspended in 100 ml double distilled sterile water and heated for 15 minutes at 100°C [5]. The mixture was boiled, then cooled and centrifuged for 15 minutes at 10,000 rpm.…”
Section: Preparation Of Microalgal Extractmentioning
confidence: 99%